The influence of boar breed and applied method on the meat content - Radović Čedomir; Gogić Marija; Radojković Dragan; Živković Vladimir; Stojiljković Nenad; Parunović Nenad; Savić Radomir (Biotechnology in Animal Husbandry, 2020)
The aim of this study was to determine the influence of the applied method of the quality carcass in 201 descendants, both sexes (n=108 male castrated animals and n=93 females), of studied boar-sires. For the determination of the meat yield (JUS1) and the share of meat (JUS 2) in carcass sides, on the basis of the performed measurements, tables for meat pigs, which are an integral part of the Rulebook on the quality of slaughtered pigs and categorization of pork meat (OG SFRY, 1985), were used. Share of meat (EC 94 and EC 06) was determined on cooled left carcass sides by method of partial dissection (according to methodology recommended by EU-Walstra and Merkus, 1996). Research was carried out on pig farm and in experimental slaughterhouse of the Institute for Animal Husbandry, Belgrade-Zemun. Housing, care and nutrition of animals were in accordance to breeding technology in investigated herd. The average share of meat determined by the application of the Rulebook (JUS2) was 43.58% with a lower absolute variation compared to the EU regulation from 1994 (EC 94; 53.56%) and from 2006 (EC 06; 56.55%). The estimated lean meat content by the application of the Rulebook (JUS 2) was by 9.98% lower compared to the EC 94 regulation and by 12.97% lower compared to EC 06. If we are talking about the selection of offspring for breeding, if we consider only the estimated leanness, we see that within the Landrace (L) breed we have high and very significant (P<0.001) differences between the sires for the assessed meat content according to EC 94 and EC 06. By implementing new methods of assessment of lean meat content (EC 94 and EC 06), a higher share of meat (9.98% respectively 12.97%) was determined compared to the Rulebook (1985). This research indicates the necessity of changing the current method for the establishment of meat content of pigs in the Republic of Serbia.